In love & trouble ebook Stories of black women. - Walker, Alice (Open Road Media, 2011)
Short fiction about the female experience from the New York Times –bestselling author of The Color Purple , “one of the best American writers of today” ( The Washington Post ).  Here are stories of women traveling with the weight of broken dreams, with kids in tow, with doubt and regret, with memories of lost loves, with lovers who have their own hard pasts and hard edges. Some from the South, some from the North, some rich and some poor, the characters that inhabit In Love & Trouble all seek a measure of self-fulfillment, even as they struggle with difficult circumstances and limiting social conventions.  The stories that make up Alice Walker’s debut short fiction collection reflect her tenacious commitment to face brutal and sometimes melancholy truths while also illuminating the ways in which the courageous pursuit of love brings hope to even the most harrowing lives.     This ebook features an illustrated biography of Alice Walker including rare photos from the author’s personal collection.